The county in Kentucky history - Ireland, Robert M., 1937- (Kentucky Bicentennial bookshelf., 2009)
In the nineteenth century, Kentucky was one of the nation's leading producers of racehorses, whiskey, tobacco -- and new counties. By 1886 the three original Kentucky counties had been carved into 119 (belated 120th was to be formed in 1912). These small divisions commanded the fierce loyalty of their citizens and for most Kentuckians formed the center of political and community life. The County in Kentucky History shows the bitter strife of countywide feuds and the conviviality of court day, the sporadic outbreaks of ill-feeling between town and country and the high-spirited brawls that regul.